Dose-dependent effect of Resveratrol on bladder cancer cells: Chemoprevention and oxidative stress - Stocco, Bianca; Toledo, Karina [UNESP]; Salvador, Mirian; Paulo, Michele; Koyama, Natalia; Torqueti Toloi, Maria Regina (Elsevier B.V., 2012)
Background: Over 6 million people die annually in the world because of cancer. Several groups are focused on studying cancer chemoprevention approaches. Resveratrol, a polyphenol, at high dosages, has been reported as antitumor and chemopreventive. However, it has a dose-dependent effect on cell death, even on some cancer cells.Objectives: Our aim was to investigate this dose-dependent effect on human bladder carcinoma ECV304 cells during oxidative stress condition.Methods: For this purpose. ECV304 cells incubated with different Resveratrol concentrations were analyzed as for their metabolic rate, membrane permeability, DNA fragmentation, anti/proapoptotic protein levels and phosphatidylserine exposure after oxidative stress.Results: Resveratrol induced cell death at high concentrations (>20 mu M), but not at low ones (0.1-20 mu M). Pretreatment with 2.5 mu M protected the cells from oxidative damage, whereas 50 mu M intensified the cell death and significantly increased Bad/Bcl-2 ratio (proapoptotic/antiapoptotic proteins). Resveratrol was able to modulate NO and PGE(2) secretion and performed an anti-adhesion activity of neutrophils on PMA-activated ECV304 cells.Conclusions: Resveratrol at high doses induces cell death of ECV304 cells whereas low doses induce protection. Modulation of Bcl-2 protein induced by Resveratrol could be mediating this effect. This information about the role of Resveratrol on cancer alerts us about its dose-dependent effects and could lead the design of future chemoprevention strategies. Published by Elsevier B.V.
Keywords: Resveratrol; Oxidative stress; Cell death; Cancer